Study of Some Biochemical Parameters of Tuberculosis Patients InThi-Qar Province/Iraq - Majida G. Magtooph; Rawa A. Hussein; Raid M. H. Al-Salih; Zaman K.Hanan (University of Thi-Qar Journal of Science, 2019)
The current study was designed,to estimate of, serum sugar, serum urea and lipid profile of tuberculosis patients in comparison with healthy subjects .Twenty eight TB patients (15 men and 13 female) random, and twenty three healthy subjects(13 men and 10 female) (control group) were used in this study. The results showed that serum sugar was non significantly (p<0.89) higher than control group, serum sugar value was raised with increase of age , and it  was no significantly  increased (P<0.909) in Women compared with Men. While, the serum urea was significantly lower (P<0.000) than control group , serum urea level was decreased with increase of age and it was no significantly increased (p<0.189) in Men compared with Women. Serum cholesterol in TB patients were no significantly (P<0.505) higher than healthy subjects , TC level was decreased with increase of age  and it was no significantly increased (P<0.418) in Women compared with Men .Tiglycerides (TG) was no significantly (P<0.085)  lower than healthy subjects,. TG level was no differences with the age, and it was non significantly increased (P<0.394) in Women compared with Men. High density lipoproteins (HDL) was no significantly lower (P<0.154 ) than healthy subjects,. HDL level was no differences with the age, and it was no significantly increased (P<0.019) in Women compared with Men. Low density lipoproteins LDL in TB patients were no significantly (P<0.634) higher than healthy group, LDL level was significantly decreased with increase of age and it was no significantly increased (P<0.577) in Men compared with Women. very low density lipoproteins (VLDL)  was no significantly lower (P<0.89) than healthy subjects,.VLDL level was no differences with  the age, and it was no significantly increased (p< 0.394)in Women compared with Men.